THE EFFECT OF ADDING GELATIN AND SALT SOLUTION TO OFF-GRADE SAPODILLA JELLY CANDY THROUGH THE PROCESS OF REDUCING ITS TANNIN CONTENT - Siti Hanifah Khairun Nisa; Mohammad Djali; Yana Cahyana (Food ScienTech Journal, 2021)
The young sapodilla fruit will take when harvesting is brownish green and has an astringent taste, called off-grade sapodilla fruit. The astringent taste of the fruit is due to the high tannin content. Soaking with a salt solution is a treatment done to reduce the astringent taste so that the fruit can continue as raw material for making jelly candy. Gelatin is added as a gelling agent to get a good jelly candy. This study aimed to determine the effect of adding gelatin used in the manufacture of off-grade sapodilla fruit jelly candy, which has been studied for its tannin content reduction. The research method used is an experimental method followed by a Factorial Randomized Block Design (RAK) test consisting of 6 treatments. The tested treatment consisted of two factors: the first factor was soaking sapodilla off-grade with variations in salt solution of 2%, 4%, and 6%, and the second factor was gelatin concentration of 18% and 20%. The results showed that the off-grade sapodilla sample gave the greater salt concentration was given, the more the salt could reduce the amount of tannin content. In jelly candy, the tannin content obtained was decreased compared to the tannin content of off-grade sapodilla fruit. The tannin is due to the unstable or too high cooking temperature. Based on the results of the texture test, found that the L2G2 treatment (4% salt solution, 20% gelatin) was closest to the commercial texture, while based on the organoleptic test, the L3G1 treatment (6% salt solution, 18% gelatin) had the highest value by the panellists.